ANALISIS KELAYAKAN FINANSIAL USAHA PEMBENIHAN IKAN NILA LARASATI (0REOCHROMIS NILOTICUS) STUDI KASUS USAHA BAPAK MALIK DI DESA KOTALINTANG ACEH TAMIANG - Kartika Sari, Kartika Sari; Mahyuddin, Thursina; Supritiswendi, Supritiswendi (grafting, 2024)
This study aims to analyze the financial feasibility of Mr. Malik's Larasati Tilapia (Orechromis niloticus) Hatchery in Kotalintang Village, Aceh Tamiang. This study uses a case study method and is analyzed descriptively quantitatively using Microsoft Excel tools. Data collection methods used are primary data and secondary data. Respondents in this study were Mr. Malik as the owner and manager of the Larasati Tilapia (Orechromis niloticus) hatchery business. The analysis that is calculated is Production Cost, Revenue, Profit, Net Present Value (NPV), Net B/C, Internal Rate Of Return (IRR), and Payback Period. The results obtained from this study are as follows: 1) The investment cost incurred is IDR 37,490,000. total production costs incurred Rp.121,027,000. Total Revenue of IDR 258,500,000. The profit earned is IDR 137,473,000. 2) Net Present Value (NPV) of IDR 53,418,844 is greater than 0, Net B/C Ratio of 2.42 greater than 1, Internal Rate Of Return (IRR) of 50.58% greater than the interest rate of 10.5%, and Payback Period (PP) of 2.2 years less than 5 years so it can be concluded that it can be concluded that Mr. Mailik's larasati tilapia hatchery in Kotalintang Village, Aceh Tamiang is feasible to run or continue because it is profitable for Mr Malik.